Sociology ... - Finsterbusch, Kurt (Guilford, Ct. : Dushkin Publ. Group.)
Vols. for <80/81-> include a study guide.
90/91 (1990; 241 p.) ; 94/95 (1994; 23rd ed.; 240 p.) ; 95/96 (1995; 240 p.) ; 96/97 (1996; 240 p.)
Keywords: Sociology; United States -- Social conditions